Crystal property and spectroscopic investigation on electro-optic and physico-chemical properties of NLO crystal; 3-(3, 4-Dihydroxyphenyl)-L-Alanine. Issue 12 (December 2019) - Vidhya, D.; Ramalingam, S.; Periandy, S.; Aarthi, R.
Abstract: In this attempt, in order to obtain high-quality NLO crystal, organic compound; 3-(3, 4-Dihydroxyphenyl)-L-Alanine crystal was fabricated. The organic-composite crystal was characterized by crystallographic and spectroscopic tools. The NLO supported parameters like crystal lattice (orthorhombic) and space group ( P 21 21 21 ) examined and validated by XRD examination. The SHG test was carried out and SHG efficiency was calculated that1.29 and 1.35 times greater than solid KDP crystal. The laser damage threshold energy density was determined to be 14.51 GW/cm 2 . By the application of mulliken charge assignment, multiple dielectric cavities were found in crystal material which is able to process the high degree of birefringence gradient. The oscillating chemical potential movement was observed by examining chemical shift, among the core carbons of hexagonal ring and bridge carbons of chain. The chemical softness insists the binding viability of further ligand groups. The π and δ-conjugated interactive complex orbitals recognized on molecular site and participation in optical active mechanism was identified. UV-Visible transmission characteristics of crystal were studied and UV-Visible absorption on degenerate energy states was noted and its band gap energy was estimated. The CT complex of the present case was acknowledged to be COOH group and it causing crystal properties of current organic composite. The hyperactive polarizability was determined as 1775.05 × 10 −33 esu and it was found to be five times greater than thiourea. The depletion energy between highly electrophilic zones and protonic zones was estimated to be ±5.241 e 2 causing permanent dielectric characteristics for the title organic composite. The non-superposable on the molecular mirror image was displayed and thereby optical ability was validated. Abstract : Nonlinear physics; Optics; Organic chemistry; 3-(3, 4-Dihydroxyphenyl)-L-Alanine; Birefringence; Laser damage threshold; CT complex; Electrophilic; Non-superposable; NLO activity